Using an Instagram campaign to influence knowledge, subjective norms, perceived behavioral control, and behavioral intentions for sustainable behaviors - Varni, Alexander; Thai, Chan L.; Jamaleddine, Sandra (Frontiers in Psychology, 2024)
Climate change poses one of the most pervasive threats to the planet today. Intervention is required to promote pro-environmental behaviors among individuals to curb its effects. Borrowing several constructs from the Theory of Planned Behavior, we designed and evaluated a campaign, delivered primarily through Instagram, to shift sustainability-related cognitions and behaviors among university students. An online survey was distributed to undergraduate students at a Northern California university and collected responses from 1,552 participants. Comparing students who self-reported exposure to the campaign with those who were not exposed, students who observed the campaign materials had more knowledge about (p<.001), greater perceived social norms about (p<.001), and greater intentions to perform sustainable behaviors (p<.001). There were also increases in sustainable behaviors during the campaign, compared to the previous academic term. Implementing campaigns inspired by behavior change theories may be one viable strategy to increase individual sustainable behaviors for climate change mitigation.